Concepts of Hyperloop Wireless Communication at 1200 km/h: 5G, Wi-Fi, Propagation, Doppler and Handover - Ali Tavsanoglu; César Briso; Diego Carmena-Cabanillas; Rafael B. Arancibia (Energies, 2021)
The new generation of capsules that circulate through vacuum tubes at speeds up to 1200 km/h, which is being developed, demands communication systems that can operate at these speeds with high capacity and quality of service. Currently, the two technologies available are the new generation of 802.11ax networks and 5G NR. Using these technologies at such high speeds in a confined environment requires a careful study and design of the configuration of the network and optimization of the physical interface. This paper describes the requirements for critical and business communications, proposing a WLAN and 5G network design based on the analysis of the propagation characteristics and constraints of vacuum tubes and using propagation measurements and simulations made in similar environments at frequencies of 2.5/5.7/24 GHz. These measurements and simulations show that propagation losses in this environment are low (4–5 dB/100 m), as a consequence of the guided propagation, so that the use of bands is preferred. Finally, considering the propagation constraints and requirements of a Hyperloop system, a complete wireless communication system is proposed using two networks with 802.11 and 5G technology.